Potential coconut coir fiber as soil reinforcement - Razali, Mohd Aris; Yahya, Nur Faezah; Tuan Ismail, Tuan Noor Hasanah (2020)
Coconut coir fibre (CCF) is one of the natural fibres abundantly available in tropical regions and is extracted from coconut fruit's husk. Coconut coir fibre will be used as reinforcement material to reduce waste material and save the environment. This research will evaluate the effect of load on coconut coir fibre's tensile properties using a different diameter a 0.2 mm, 0.3 mm, 0.4 mm, 0.5 mm, and 0.6 mm with the same length of 0.7 mm. The tensile test will be carried out to determine the properties of coconut coir fibre. The research carried out and the conclusions drawn by different researchers in the last few decades are also briefly presented. The ultimate tensile strength value base on the graph has been obtained with 0.2 mm and 0.6mm. The high ultimate tensile strength is 88.30 MPa at 0.6 mm diameter of CCF. It can be concluded the diameter of the CCF will affect the strength of the reinforcement. Coconut fibres reinforced composites have been used as cheap and durable non-structural elements. This review aims to spread awareness of coconut fibres as a construction material in civil engineering.